Chromium-Salophen as a Soluble or Silica-Supported Co-Catalyst for the Fixation of CO2 Onto Styrene Oxide at Low Temperatures - Balas, Matthieu; K/Bidi, Ludivine; Launay, Franck; Villanneau, Richard (Frontiers in Chemistry, 2021)
Addition of a soluble or a supported CrIII-salophen complex as a co-catalyst greatly enhances the catalytic activity of Bu4NBr for the formation of styrene carbonate from styrene epoxide and CO2. Their combination with a very low co-catalyst:Bu4NBr:styrene oxide ratio = 1:2:112 (corresponding to 0.9 mol % of CrIII co-catalyst) led to an almost complete conversion of styrene oxide after 7 h at 80°C under an initial pressure of CO2 of 11 bar and to a selectivity in styrene carbonate of 100%. The covalent heterogenization of the complex was achieved through the formation of an amide bond with a functionalized NH2-SBA-15 silica support. In both conditions, the use of these CrIII catalysts allowed excellent conversion of styrene already at 50°C. Comparison with our previous work using other metal cations from the transition metals particularly highlights the preponderant effect of the nature of the metal cation as a co-catalyst in this reaction.